2018
DOI: 10.4103/ijp.ijp_21_17
|View full text |Cite
|
Sign up to set email alerts
|

Is tapentadol a potential Trojan horse in the postdextropropoxyphene era in India?

Abstract: Tapentadol is a centrally acting opioid analgesic which has partial opioid agonistic and norepinephrine reuptake inhibitor action similar to its nearest congener and tramadol though with a relatively higher μ-affinity. It has abuse potential, is a scheduled drug, yet currently is not known to be an opioid widely misused in India. However, under the current drug abuse legislation in India, where common prescription opioids such as dextropropoxyphene have been banned, tapentadol may take the center stage of phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In 2017, our centre was the subject of a single peerreviewed study detailing two incidences of abuse. 41 The Indian Pharmacovigilance Program has issued no drug safety alerts or advisories, and Tapentadol's current drug label does not indicate that it is a class H or H1 substance. 42 Tapentadol is more likely than Tramadol to be abused.…”
Section: Drug Abusementioning
confidence: 99%
“…In 2017, our centre was the subject of a single peerreviewed study detailing two incidences of abuse. 41 The Indian Pharmacovigilance Program has issued no drug safety alerts or advisories, and Tapentadol's current drug label does not indicate that it is a class H or H1 substance. 42 Tapentadol is more likely than Tramadol to be abused.…”
Section: Drug Abusementioning
confidence: 99%
“…Tapentadol: 2016 Diversion and illicit sale of extended release tapentadol in the United States [ 456 ] ; literature review on tramadol related scientific studies [ 457 ] 2017 Systematic review and meta-analysis of the efficacy and safety of tapentadol [ 458 ]; synthetic routes towards homochiral tapentadol [ 459 ]; 2018 efficacy and safety of tapentadol prolonged release formulation [ 460 ]; assessment of tapentadol API Abuse Liability [ 461 ]; review of tapentadol [ 462 ]; incorporation of tapentadol into validated screening and quantitative methods [ 463 ]; HPLC method (LC-MS compatible) developed and validated for identification and characterization of tapentadol and degradation products [ 464 ]; 2019 electrochemical sensor for determination of tapentadol in the presence of paracetamol in pharmaceutical samples [ 465 ]; optical, thermal, spectroscopic and structural analyses of the phase transformation occurring in tapentadol hydrochloride was studied using single-crystal X-ray diffraction, differential scanning calorimetry and Raman scattering measurements [ 466 ].…”
Section: Routine and Improved Analyses Of Abused Substancesmentioning
confidence: 99%
“…This may contribute to explaining both tapentadol’s higher central nervous system (CNS) activity and detrimental effects. Indeed, although less than with other potent opioids, tapentadol’s prominent MOR agonism is associated with mood alterations and euphoria and, thus, with dependence and abuse potential [ 26 , 27 ]. A study with occasional opioid users showed that, unlike tramadol, therapeutic doses of tapentadol led exclusively to positive subject-rated effects, with faster onset and offset than other opioids, which may contribute to a greater frequency of use [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%